Development of an ideal starch saccharification process using amylolytic enzymes from thermophiles. (1st April 2004) - Satyanarayana, T.; Noorwez, S.M.; Kumar, S.; Rao, J.L.U.M.; Ezhilvannan, M.; Kaur, P.
Abstract : The extensive efforts to screen thermophilic fungi and bacteria, isolated from various environmental samples, have resulted in the selection of Thermomucor indicae-seudaticae, Geobacillus thermoleovorans NP33 and G. thermoleovorans NP54 for the production of glucoamylase, amylopullulanase and α-amylase, respectively. Submerged and solid-state fermentation processes were optimized for maximizing the secretion of glucoamylase by T. indicae-seudaticae . The production of amylopullulanase and α-amylase by NP33 and NP54 in submerged fermentation was also optimized. Glucoamylase was optimally active at pH 7.0 and 60°C and was shown to saccharify soluble as well as raw starches. Amylopullulanase and α-amylase exhibited optima at pH 7.0 and 100°C and saccharified starch efficiently. Differential inhibition and action on mixed substrates clearly suggested that there are two separate active sites for α-amylase and pullulanase activities of amylopullulanase. Both α-amylase and amylopullulanase are high maltose-forming and Ca 2+ -independent. These amylolytic enzymes have been shown to be useful in starch saccharification alone and in combination.